2018
DOI: 10.1016/j.rboe.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

APSI scaphoid hemiarthroplasty – long-term results

Abstract: ObjectiveThis study is aimed at evaluating the long-term results of proximal scaphoid hemiarthroplasty for post-traumatic avascular necrosis at this institution.MethodsTwelve patients who underwent this procedure were identified, and the mean follow-up time was 6.5 years (range: 5–8 years). All patients were male, with a mean age of 39 years (range: 28–55 years). In eight patients, the non-dominant limb was affected. The procedure was carried out through a dorsal approach and all patients underwent the same re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…All procedures were performed using a dorsal approach 4,[12][13][14]16 except two studies: One used a volar approach in 4/41 cases and lateral in 2/41 cases, 15 the second performed arthroscopic scaphoidectomy. 7 Associated stiloidectomy was performed in four studies 4,12,13,15 for a total of 87/118 (73%) patients; two studies did not perform stiloidectomy, 7,16 and one 14 performed the stiloidectomy, but the percentage was not reported. A dorsal capsulodesis was performed in two studies-eight of 39 patients (20%) 13 and all patients 36/36.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All procedures were performed using a dorsal approach 4,[12][13][14]16 except two studies: One used a volar approach in 4/41 cases and lateral in 2/41 cases, 15 the second performed arthroscopic scaphoidectomy. 7 Associated stiloidectomy was performed in four studies 4,12,13,15 for a total of 87/118 (73%) patients; two studies did not perform stiloidectomy, 7,16 and one 14 performed the stiloidectomy, but the percentage was not reported. A dorsal capsulodesis was performed in two studies-eight of 39 patients (20%) 13 and all patients 36/36.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies recommended three weeks wearing full time a spica splint before beginning rehabilitation of the wrist. 4,12,[14][15][16] Aribert suggested a shorter immobilization of 2 weeks, while Gras et al suggested an immediate ROM at home.…”
Section: Rehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The prosthetic replacement of the scaphoid represents an alternative to more invasive surgical techniques 1 such as partial scaphoidectomy with removal of the proximal fragment which generally leads to a carpal collapse, resection of the first carpal row with risk of progression of arthritis and reduction in the grip strength, 4-corner fusion or total prosthetic replacement of the wrist which is indicated in case of radiocarpal and intercarpal generalized arthritis, and associated with a reduction in the range of movement. 2,3 The scaphoid implants allow the radiocarpal biomechanics to be restored, treating only the injured bone, and allowing the most invasive surgical operations to be performed subsequently, in case of failure. 4 The adaptive proximal scaphoid implant (APSI) is a partial scaphoid prosthesis, ovoid and unfixed, which replaces the proximal pole of the scaphoid.…”
Section: Introductionmentioning
confidence: 99%